2018
DOI: 10.1063/1.5036757
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron spectroscopy of anthracene and fluoranthene radical anions

Abstract: We report the slow electron velocity map imaging spectroscopy of cryogenically cooled anthracene and fluoranthene radical anions, two similarly sized polycyclic aromatic hydrocarbon molecules. The results allow us to examine the lowest energy singlet and triplet states in the neutral molecules on equal footing from the anionic ground state. The analysis of the experimental spectra is aided by harmonic calculations and Franck-Condon simulations, which generally show good agreement with experimental values and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 40 publications
7
33
0
Order By: Relevance
“…presented a very high resolution slow-electron PE imaging of C14H10 -. 23 The PE spectra by Song et al at wavelengths of 532, 610 and 700 nm contained evidence of indirect detachment features that were red-shifted relative to the direct detachment peak accessing the neutral ground state. 22 The spectral range over which this indirect band appeared was consistent with the vertical excitation energy reported for a * resonance, from which autodetachment can occur.…”
Section: Please Cite This Article As Doi:101063/50007470mentioning
confidence: 97%
See 3 more Smart Citations
“…presented a very high resolution slow-electron PE imaging of C14H10 -. 23 The PE spectra by Song et al at wavelengths of 532, 610 and 700 nm contained evidence of indirect detachment features that were red-shifted relative to the direct detachment peak accessing the neutral ground state. 22 The spectral range over which this indirect band appeared was consistent with the vertical excitation energy reported for a * resonance, from which autodetachment can occur.…”
Section: Please Cite This Article As Doi:101063/50007470mentioning
confidence: 97%
“…33 Dessent used anthracene as a test molecule in a DFT benchmark study of the ground state vibrational properties of the neutral and anion, 29 and Kreger et al showed good agreement between their DFT calculations and vibrational structure in the high-resolution PE spectra. 23 Malloci et al…”
Section: Please Cite This Article As Doi:101063/50007470mentioning
confidence: 99%
See 2 more Smart Citations
“…9c), peaks a (27 1 ), b (26 1 ), c 27 2, and e (25 1 ), which are symmetry-forbidden in the non-resonant spectra. 5 Vibronic coupling or Herzberg-Teller coupling 4,63,72,89 has been previously invoked to explain the observations of FCinactive vibrational modes or anomalous vibrational intensities in non-resonant PES. While we cannot rule out the effects of vibronic coupling for the appearance of the low-frequency FCinactive and symmetry-forbidden bending modes in the resonant PE spectra shown in Fig.…”
Section: Intramolecular Inelastic Scatteringmentioning
confidence: 99%